Zaklade u Hrvatskoj : uloga, razvoj i postignuća - Bežovan, Gojko (Array, 2008)
The paper is the result of an action-oriented empirical research about the role, development and achievements of foundations n Croatia. As a background for empirical research, the secondary sources were analysed, as well as the results of previous research studies on the development of foundations in Croatia. The theoretical analytical framework of the development of foundations in Croatia is connected with the contemporary typology of the role of foundations and the social model of the development of foundations. This paper also outlines the developmental problems and achievements of foundations in some transitional countries. The aims of the research are to contribute to a better understanding of the environment for the development of foundations in Croatia, to explain the role and vision of the development of foundations, to estimate strengths and weaknesses of foundations and to stimulate a discussion about the role of foundations in the development of Croatia. The data on foundations were collected through a mail survey and case studies. The results of the research mainly speak of the development and the increase in the number of foundations in Croatia that mostly play a complementary role. To a smaller extent, foundations appear as innovators. The results of the research indicate a peripheral social model of the development of foundations. Scholarship foundations and foundations in the area of social welfare are dominant. Foundations encounter problems in raising funds to increase their basic assets. They are mainly managed on volunteer basis, and the state does not appear as a partner in the development of foundations. The development of foundations in Croatia will largely depend on the economic progress and new middle classes that will be more concerned about social problems